(untitled) - Loshin, David S. (Boston, 1991)
This workbook is designed to supplement optics textbooks and covers all the traditional topics of geometrical optics. Terms, equations, definitions, and concepts are discussed briefly and explained through a series of problems that are worked out in a step-by-step manner which simplifies the problem-solving process. Additional practice problems are provided at the end of each chapter.
Keywords: Geometrical optics,Optometry,Quang hình học,Phép kiểm định; Problems, exercises, etc.,Problems, exercises, etc.,Vấn đề, bài tập, v.v.,Vấn đề, bài tập, v.v.